School Supervisors as Key in Improving the Managerial Competencies of Principals and Teachers in Aceh Besar - Murza, Cut Ika; AR, Murniati; Usman, Nasir (Pascasarjana Universitas KH. Abdul Chalim, 2025)
School supervisors play a crucial role in maintaining the quality of education, particularly in enhancing the managerial competencies of principals and teachers. Through supervision and oversight, supervisors ensure that the teaching and school management processes comply with established standards. This study aims to analyze the role of supervisors in improving the managerial competencies of principals and teachers in Aceh Besar Regency. The research uses a qualitative approach with a case study method. The research subjects consist of 18 individuals, including 3 school supervisors, 3 principals, and 12 teachers from three elementary schools: SDN Lambada Klieng, SDN Labuy, and SDN Ruyung. The subject selection was conducted using purposive sampling, aimed at gaining in-depth insights into the role of supervisors in enhancing the quality of education. Data were collected through in-depth interviews, observations, and documentation, and analyzed using qualitative data analysis techniques, which include data reduction, data presentation, and conclusion drawing. The research findings indicate that supervisors play an important role in providing support to principals and teachers through training, supervision, and effective monitoring. The supervision carried out by school supervisors has proven to improve the managerial competencies of principals, as well as enhance the professionalism and quality of teaching among teachers. This study suggests the importance of the active role of supervisors in capacity-building programs for teachers and principals to achieve better education quality in Aceh Besar.